Biological Nutrient Removal of Domestic Sewage Using Combined Anaerobic-Anoxic-Aerobic Reactor - Ismail, Maheran (2001)
The overall objectives of this study is to develop an innovative technology to treat nutrients especially nitrogen and phosphorus in domestic wastewater. This process is called the Anaerobic-anoxic-aerobic (AAA). Biological nitrificationdenitrification and phosphorus removal in a single reactor have been shown applicable to treat nutrients with some modification in an aerobic zone, where 'cosmo-ball' media were introduced to enhance bacterial growth. The vertical reactor with 'up flow' influent was operated using a continuous system with an anaerobic-anoxic-aerobic zone sequence. This experiment was operated at HRT total of 7 hours where the anaerobic, anoxic and aerobic zone takes 1.5, 1.5 and 4 hours respectively. The experimental run was conducted in the Environmental laboratory using raw samples from an Extended Aeration treatment plant at Serdang Raya, Sri Kembangan, Selangor. The results showed that nitrification denitrification process could be achieved using this anaerobic-anoxic-aerobic (AAA) reactor with 63% NH4-N removal and 51 % P04 removal. Removal of BOD, COD, TSS, VSS were 84%, 78%, 85% and 83% respectively. The results obtained also shows that organic and pH has significance effects on nutrient removal for a medium strength wastewater. The treatment of sewage effluent was also carried out in anaerobic-anoxic-aerobic reactor to study the kinetics parameters for nitrification and denitrification processes and the results obtained were: YN = 0.041 mg VSS/mg NH4, KI = 0.0417 dail, 11m = 1.6470 day-l, KN = 0.8996 mg/l (kinetic parameter for denitrification). Meanwhile parameters kinetic for denitrification were: Y D = 0.017 mg VSS/mg N03, KIl = 0.0014 dail, I1ml = 0.00407 dail, KD = 8.036 mg/l. It has been found that the reactor was succeeded in removing nutrients from sewage samples.